Preliminary Results of the Kuznetsk Coal Basin Cover Deposits Radon Hazard Assessment - Timofey Leshukov; Konstantin Legoshchin; Elizaveta Baranova; Aleksey Larionov (Geosciences)
The study of the influence of geological structure (e.g., faults) on radon emanations is usually applicable provided that there are conditionally background (control) territories with which radon indicators will be compared. In the presented study, we selected an area where pre-Cenozoic faults that could potentially be associated with the radon hazard of the Kuznetsk coal basin were not identified. The cover deposits in the study area are represented by loamy and clayey strata overlying the Paleozoic sedimentary cycles. The radon field was estimated based on the radon flux density (RFD) and radon activity concentration (RAC) in the soil gas. The RAC was measured in two ways—by the sorption method on activated carbon and by the method of active sampling of soil gas from a borehole. At the same time, the role of meteorological conditions and the physical properties of the soil in the radon field was assessed. Our study shows that local variations in the physical properties of the soil are insignificant and do not have a significant effect on the RAC in the soil gas of the Kuznetsk coal basin, with the exception of soil moisture. High values of RAC in the territory considered as conditionally background, in the absence of pre-Cenozoic faults, suggest other causes (the presence of the latest Neogene–Quaternary faults, high concentrations of 226Ra, or other insufficiently studied causes). Due to the absence of faults, it is possible to assume a diffusion type of radon transfer in the geological environment, which indicates a shallow source of radon in such high concentrations. Our results indicate that studies of the 226Ra content and additional studies of the radon hazard of similar areas should also be carried out.